Temporal upscaling of instantaneous evapotranspiration on clear‐sky days using the constant reference evaporative fraction method with fixed or variable surface resistances at two cropland sites. Issue 2 (25th January 2017) - Tang, Ronglin; Li, Zhao‐Liang; Sun, Xiaomin; Bi, Yuyun
Abstract: Surface evapotranspiration (ET) is an important component of water and energy in land and atmospheric systems. This paper investigated whether using variable surface resistances in the reference ET estimates from the full‐form Penman‐Monteith (PM) equation could improve the upscaled daily ET estimates in the constant reference evaporative fraction (EFr, the ratio of actual to reference grass/alfalfa ET) method on clear‐sky days using ground‐based measurements. Half‐hourly near‐surface meteorological variables and eddy covariance (EC) system‐measured latent heat flux data on clear‐sky days were collected at two sites with different climatic conditions, namely, the subhumid Yucheng station in northern China and the arid Yingke site in northwestern China and were used as the model input and ground‐truth, respectively. The results showed that using the Food and Agriculture Organization (FAO)‐PM equation, the American Society of Civil Engineers‐PM equation, and the full‐form PM equation to estimate the reference ET in the constant EFr method produced progressively smaller upscaled daily ET at a given time from midmorning to midafternoon. Using all three PM equations produced the best results at noon at both sites regardless of whether the energy imbalance of the EC measurements was closed. When the EC measurements were not corrected for energy imbalance, using variable surface resistance in the full‐form PM equation could improve the ET upscaling in the midafternoon, but worse results may occur in the midmorning to noon. Site‐to‐site and time‐to‐time variations were found in the performances of a given PM equation (with fixed or variable surface resistances) before and after the energy imbalance was closed. Key Points: The constant reference evaporative fraction upscaling method was tested Fixed and variable surface resistances were compared in the ET upscaling Analysis was made over different assumed satellite overpass times